HUBUNGAN ANTARA PEMAKAIAN ALAT KONTRASEPSI SUNTIK DENGAN HIPERTENSI PADA AKSEPTOR KB SUNTIK DI PUSKESMAS HARAPAN RAYA PEKANBARU - Wiwik - Norlita; Isnaniar - -; Elfika - Shafitri (LPPM Universitas Muhammadiyah Riau, 2018)
Hormonal contraceptives such as injectable contraceptives can cause changes in blood pressure. The purpose of this study was to determine the relationship between the use of injectable contraceptives and blood pressure in injectable family planning acceptors at Puskesmas Harapan Raya Pekanbaru. The type of research used is Cross Sectional with accidental sampling sampling technique where the sample in this study were mothers who were found visiting a family planning clinic at Puskesmas Harapan Raya Pekanbaru which amounted to 32 respondents. The results of the study were carried out on July 13-28, 2018, with chi-square statistical tests obtained with normal blood pressure of 25 respondents, hypertension of 7 respondents, and the relationship between types of injectable birth control used with blood pressure (p-value> 0.05) with p value = 0.084. Conclusion there is no significant relationship between the use of injectable contraceptives and blood pressure in injectable family planning acceptors at Puskesmas Harapan Raya Pekanbaru.